Human Capital as a Tool for Predicting Development of Transport and Communications Sector: The Czech Republic Perspective - Gottwald, Dalibor; Svadlenka, Libor; Lejskova, Pavla; Pavlisova, Hana (Communications - Scientific letters of the University of Zilina, 2017)
Human capital as a part of intellectual capital has crucial impact on the overall development of all sectors of national economy. This trend can also be confirmed by the growing number of academic papers dealing with the issue. This paper presents results of a questionnaire survey that investigated the human capital in terms of selected motivational factors and employability prospects as seen by students of high schools programs related to transport and communications. The main objective was to get an insight into the current situation in the sector and its attractiveness as seen by potential future employees. The questionnaire survey was carried out in April 2016 and its respondents were future high school graduates, who can either continue to study transport and communications at university or enter the job market and search for a job in the sector straight away. Results obtained from a series of statistical tests using the Two-way ANOVA method can serve both companies and educational institutions as a basis for implementation of measures that would guarantee sustainable development of human resources in this field.